Impact of histologic chorioamnionitis on pulmonary hypertension and respiratory outcomes in preterm infants. (1st March 2018) - Yum, Sook Kyung; Kim, Min‐Sung; Kwun, Yoojin; Moon, Cheong‐Jun; Youn, Young‐Ah; Sung, In Kyung
Abstract : We aimed to evaluate the association between the presence of histologic chorioamnionitis (HC) and development of pulmonary hypertension (PH) during neonatal intensive care unit (NICU) stay. Data of preterm infants born at 32 weeks of gestation or less were reviewed. The development of PH and other respiratory outcomes were compared according to the presence of HC. Potential risk factors associated with the development of PH during NICU stay were used for multivariable logistic regression analysis. A total of 188 infants were enrolled: 72 in the HC group and 116 in the no HC group. The HC group infants were born at a significantly shorter gestational age and lower birthweight, with a greater proportion presenting preterm premature rupture of membrane (pPROM) > 18 h before delivery. More infants in the HC group developed pneumothorax ( P  = 0.008), and moderate and severe bronchopulmonary dysplasia (BPD; P  = 0.001 and P  = 0.006, respectively). PH in the HC group was significantly more frequent compared to the no HC group (25.0% versus 8.6%, P  = 0.002). Based on a multivariable logistic regression analysis, birthweight ( P  = 0.009, odds ratio [OR] = 0.997, 95% confidence interval [CI] = 0.995–0.999), the presence of HC ( P  = 0.047, OR = 2.799, 95% CI = 1.014–7.731), and duration of invasive mechanical ventilation (MV) > 14 days ( P  = 0.015, OR = 8.036, 95% CI = 1.051–43.030) were significant factors. The presence of HC and prolonged invasive MV in infants with lower birthweight possibly synergistically act against preterm pulmonary outcomes and leads to the development of PH. Verification of this result and further investigation to establish effective strategies to prevent or ameliorate these adverse outcomes are needed.